Akibat Hukum Tindakan Akuisisi Di Sektor Pertambangan Mineral Dan Batubara Terhadap Peralihan Dan Pengendalian Izin Usaha Pertambangan - Arif Setia Sasmita, Herman Susetyo *, Hendro Saptono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Natural resources especially mineral and coal are the unrenewable resources and possess high economic value commodity in business so it should be protected by law under the government authority of the existence. But the government does not be able to explore and exploit it by itself so the government give a permission to private corporation with mining work license (IUP) to do it. But as we know that mineral and coal are the profitable sector in business so any corporate action such as acquisition may to influence of the license that given to one corporate individually because of it. Acquisition which is moved the share from corporation whom acquired by other corporation or person would be influenced its assets and business including the IUP. Therefore I will research how big its influencing the IUP. This research aimed to investigate and examine the norms and principles related to the acquisition and IUP with yuridical-normative approach. This research will be doing with descriptive analytical study and qualitative research type. Before it, I collect any legal materials that have been determined and then it used to find and determine themes and category and patterns of relationship between them so there would be comprehensive discussion about the problems and found the logical-deductive answer. From the research and study found that transfer of IUP is not same with transfer of share in the acquisition scheme because of the difference between IUP and share. Its all about the characteristic of material properties between them and also it’s process and condition to transfer it in public and private law. Displacement that occurs is just the control of the assets and corporation as big as the share that transferred. From this conclusion I give suggestion to change the share transfer arrangement by the license from the government, not just a notification because of the big influences to the IUP. Moreover, I suggested to raise higher the arrangement about the transfer of IUP from government regulation (PP) into law (UU).